Community Development and Panchayati Raj in India: Examining the Evolution and Implementation of Panchayati Raj System in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In India, the Panchayati Raj generally refers to the system introduced by constitutional amendment in 1992, although it is based upon the traditional Panchayat system of South Asia The modern Panchayati Raj and its Gram Panchayats are not to be confused with the extra-constitutional Khap Panchayat (or Caste Panchayat) found in Northern India. The Panchayati Raj system was formalized in 1992, following a study conducted by a number of Indian committees on various ways of implementing more decentralized administration.